Pengaruh Kemudahan Transaksi, Promosi Digital, dan Gaya Hidup Hedonis terhadap Perilaku Impulsive Buying Pengguna QRIS di Kalangan Mahasiswa: The Effect of Ease of Transactions, Digital Promotions, and Hedonistic Lifestyle on Impulsive Buying Behavior of QRIS Users Among Students - Nayla Faizah Zahra; Astrid Riyantoni; Chery Juniarti; Ayu Kartika Ovtavia Pardede; Atik Budi Paryanti (Jurnal Bisnis dan Ekonomi, 2026)
ABSTRACT. This study aims to analyze the influence of transaction convenience, digital promotion strategies, and hedonic lifestyle tendencies on impulsive buying behavior among university students who use QRIS in Jakarta. The digital transformation of payment systems has significantly altered consumer behavior patterns. However, the interplay between technological and psychological factors in driving spontaneous purchasing behavior still requires deeper investigation. The research employed a quantitative approach with a causal-associative design using a survey method. Data were collected through a closed-ended questionnaire utilizing a five- point Likert scale distributed to 87 students selected through purposive sampling. The data were analyzed using multiple linear regression with SPSS version 25. The findings indicate that, simultaneously, the three independent variables significantly influence students’ impulsive buying behavior. Partially, digital promotion and hedonic lifestyle show positive and significant effects, while transaction convenience does not have a significant impact. This suggests that for students in urban areas, the ease of digital payment has become commonplace and is no longer a major factor triggering impulsive purchases without the influence of promotional stimuli or a consumptive lifestyle. The coefficient of determination (R²) value of 0.686 indicates that the research model explains 68.6% of the variation in students’ impulsive buying behavior. The results highlight the importance of enhancing digital financial literacy so that students can better regulate their consumptive tendencies amid the rapid growth of the digital economy.